IDENTIFIKASI LAPISAN RAWAN LONGSOR MENGGUNAKAN METODE GEOLISTRIK RESISTIVITAS KONFIGURASI WENNER SCHLUMBERGERDI DESA PANA KECAMATAN ALLA KABUPATEN ENREKANG - Taufik, Muh.; Sahara, Sahara; Wahyuni, Ayusari (JFT : Jurnal Fisika dan Terapannya, 2017)
Has conducted research on landslide-prone layer in Pana village Alla subdistrict of Enrekang regency. This research aims to determine the subsurface structure in Pana village Alla subdistrict of Enrekang regency and to determine the potential landslides based of rock layers in Pana village Alla subdistrict of Enrekang regency. In this research measurements were performed using geolistrik resistivity method configuration of Wenner-Schlumberger. Measurements were taken at 5 tracks with the lenght of each track is 75 m with each electrode spacing is 5 m for each track. The result of data processing showed that 5 tracks composed of a layer of soil with plenty of water accumulation, with resistivity value of 0,169 Î©m-13,7 Î©m, a layer of shale in weather conditions with resistivity value of 4,16 Î©m-41,3 Î©m and a layer of shale in fresh condition with resistivity value of 41,3 Î©m-1141 Î©m. Futhermore, the track is concidered prone to landslide are track 3, track 4 and track 5. These predictions are because on the third track suspected slip surface with resistivity value of 29,7 Î©m-37,9 Î©m.